Analysis of epigenetic features characteristic of L1 loci expressed in human cells. Issue 4 (31st January 2022) - Freeman, Benjamin; White, Travis; Kaul, Tiffany; Stow, Emily C; Baddoo, Melody; Ungerleider, Nathan; Morales, Maria; Yang, Hanlin; Deharo, Dawn; Deininger, Prescott; Belancio, Victoria P
Abstract: Only a select few L1 loci in the human genome are expressed in any given cell line or organ, likely to minimize damage done to the genome. The epigenetic features and requirements of expressed L1 loci are currently unknown. Using human cells and comprehensive epigenetic analysis of individual expressed and unexpressed L1 loci, we determined that endogenous L1 transcription depends on a combination of epigenetic factors, including open chromatin, activating histone modifications, and hypomethylation at the L1 promoter. We demonstrate that the L1 promoter seems to require interaction with enhancer elements for optimal function. We utilize epigenetic context to predict the expression status of L1Hs loci that are poorly mappable with RNA-Seq. Our analysis identified a population of 'transitional' L1 loci that likely have greater potential to be activated during the epigenetic dysregulation seen in tumors and during aging because they are the most responsive to targeted CRISPR-mediated delivery of trans-activating domains. We demonstrate that an engineered increase in endogenous L1 mRNA expression increases Alu mobilization. Overall, our findings present the first global and comprehensive analysis of epigenetic status of individual L1 loci based on their expression status and demonstrate the importance of epigenetic context for L1 expression heterogeneity.